Resign or carry‐on? District and principal leadership as drivers of change in teacher turnover intentions during the COVID‐19 crisis: A latent growth model examination - Matthews, Russell A.; Wayne, Julie H.; Smith, Claire; Casper, Wendy J.; Wang, Yi‐Ren; Streit, Jessica (Journal of occupational and organizational psychology, 2022)
During the COVID‐19 pandemic, teachers in the United States, an already at‐risk occupation group, experienced new work‐related stressors, safety concerns, and work‐life challenges, magnifying on‐going retention concerns. Integrating the crisis management literature with the unfolding model of turnover, we theorize that leader actions trigger initial employee responses but also set the stage for on‐going crisis response that influence changes in teachers' turnover intentions. We apply latent growth curve modelling to test our hypotheses based on a sample of 617 K‐12 teachers using nine waves of data, including a baseline survey at the start of the 2020–2021 school year and eight follow‐up surveys (2‐week lags) through the Fall 2020 semester. In terms of overall adaptation, teachers on average, experienced an increase in work‐life balance and a decrease in turnover intentions over the course of the semester. Results also suggest that district and school leadership provide unique and complementary resources, but leader behaviours that shape initial crisis responses do not similarly affect employee responses during crisis, contrary to theory. Instead, teachers' adaptive crisis response trajectories were triggered by continued resource provision over the semester; increasing provision of valued resources (i.e., continued refinement of safety practices) and improvements in work‐life balance prevented turnover intentions from spiralling throughout the crisis. Crisis management theory and research should continue to incorporate temporal dynamics and identify factors that contribute to crisis response trajectories, using designs and analyses that allow for examination as crises unfold in real time.